Remote Predictive Mapping 2. Gamma-Ray Spectrometry: A Tool for Mapping Canada's North - Ford, K.; Harris, J.; Shives, R.; Carson, J.; Buckle, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY This paper reviews the theory, acquisition and application of gamma-ray spectrometric data for geological mapping, especially for Canada's North. Theoretical principals are reviewed and survey parameters and data acquisition procedures are discussed. Interpretation principles are then presented and various methods, utilizing computer processing, enhancement and classification procedures are introduced using many image examples. The ability of gamma-ray spectrometry to map the distribution of potassium, uranium, and thorium on the surface of the Earth provides powerful assistance for regional and local bedrock and surficial geological mapping. Important direct and indirect exploration guidance, in a wide variety of geological settings, is also provided, as is important information for environmental radiation monitoring and land-use planning.